Bizantyńska obecność na Krymie i pamięć o niej w literaturze Słowian Południowych i Wschodnich z X–XVI w. (casus biskupów-męczenników z Chersonezu Taurydzkiego) - Leszka, Mirosław J.; Brzozowska, Zofia (Vox Patrum, 2024)
The aim of this article is to present the beginnings and the development of the Eastern Christian cult – both in its Byzantine and medieval Orthodox Slavic variants – of seven Holy Martyrs: Basil, Ephrem, Eugenius, Elpidius, Agathodorus, Aetherius and Capiton, who at least from the 9th–10th century were worshipped as Bishops of Chersonesus, contributing to spreading the Eastern (Orthodox) Christianity in the region of the Crimean Peninsula. In the first part of our article we are making an attempt to reconstruct the beginnings of this cult in Byzantium and to show, to what extent the early hagiographical tradition of the Bishop-Martyrs from Chersonesus was shaped by a changing political situation in the Byzantine Empire. The second part is devoted to the Orthodox Slavic version of their cult: we are discussing here the earliest remarks about these Saints, that can be found in the Church Slavic sources, analyzing all hagiographic texts devoted to them, that have been preserved in the Eastern and South (Bulgarian and Serbian) manuscript material from the 10th–16th centuries. Some attention has been given also to images of the Seven Bishop-Martyrs from Chersonesus in the Orthodox Slavic medieval art.